Pyknotic Cell Features of Buccal Mucosal Smear in Various Oral Lesions of Betel Nut Chewers - Maulina Triani; Akbar Aulia Hidayat; Aris Aji Kurniawan; Anindita Laksitasari; Aditya Priagung Prakosa (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2022)
The habit of chewing betel nut is one of the predisposing factors that can trigger the formation of various oral lesions and develop into a malignant condition in the form of oral squamous cell carcinoma (OSCC). This malignancy has a low five-year survival rate as early detection is not widely carried out. Early detection can be conducted by examining pyknotic cells to describe the level of apoptosis. This study aims to examine the pyknotic cell features as a marker of apoptosis in various oral lesions found in betel nut chewers. This study is an analytic survey conducted once with a post-test control group design. The study was conducted on 17 betel nut chewers and 17 healthy people as controls. A buccal mucous smear was collected, and cytological slides were made with Papanicolaou stain. Pyknotic cells were counted using a light microscope and Optilab pro camera. This study found several oral lesions in betel nut chewers, namely exogenous pigmentation, lesions resembling leukoplakia, and lichenoid reaction. Furthermore, the result also showed that the frequency of pyknotic cells in betel nut chewers was lower than in the control group. Non-parametric Kruskal Wallis and post hoc Mann Whitney test showed significant differences in the number of pyknotic cells in various oral lesions with a p-value = 0,001. It can be concluded that the consumption of betel nut affected the level of apoptosis, characterized by a decrease in pyknotic cells and significantly different pyknotic cells depending on the type of oral lesions.